Sundial Horizontal dalam Penentuan Penanggalan Jawa Pranata Mangsa - Muhammad Himmatur Riza (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2018)
Sundial as a historic astronomical instrument that can be used in solving several basic astronomical problems. The "Pranata Mangsa" Javanese calendar which the determination is based on the position of the sun becomes a reliable thing to be calculated. There has been an existing method that some farmers use their feet soles to determine the first "mangsa" in "pranata mangsa" Javanese calendar. According to the author, this method doesn't produce an accurate result. Regarding to the ineffective "pranata mangsa" javanese calendar determination, sundial can be used to solve the problems of "pranata mangsa" Javanese calendar determination. A qualitative research is used in this paper with descriptive-analytic approach which aims to know the in-depth description that illustrate the concept of astronomy of the "horizontal sundial" and analyze the mathematical concept of the position of the sun and others data that are required in the determination of the "pranata mangsa" Javanese calendar. This research uses data collecting techniques through field research which is considering the horizontal sundial as a primary data and the participant observation for the observation method and experiment for finding some important data. The secondary data of the research comes from some literatures and documents in a form of books, articles and papers which is related to the research object. The finding of this research is the determination of the "pranata mangsa" javanese calendar using "horizontal sundial" method uses feet soles of a person which is reliable to get an accurate result. This is purely coming from the way how some Javanese people determine the "pranata mangsa" Javanese calendar directly in field.